Therapeutic strategies for pulmonary sarcoidosis. (2nd April 2020) - James, W. Ennis; Judson, Marc A.
ABSTRACT: Introduction : The treatment of pulmonary sarcoidosis is not standardized. Treatment involves a multi-step decision process beginning with whether treatment is warranted, determining initial therapy, then assessing when therapy requires modifications or can be discontinued. Areas covered : This manuscript will address the following issues concerning the treatment of pulmonary sarcoidosis: Treatment indications, initial anti-granulomatous therapy, therapy for chronic and fibrotic disease, glucocorticoid therapy, alternative therapy to glucocorticoids, non-granulomatous therapies, and managing complications of disease. Information was obtained through a literature search of PubMed and Web of Science databases. Expert opinion : Although glucocorticoids are highly effective for pulmonary sarcoidosis, their potential to cause significant side effects often mandates consideration of alternative agents. As the most common indication for the treatment of pulmonary sarcoidosis is quality of life impairment, traditional objective tests of lung function and radiographic imagining often have a minor role in therapeutic decision-making. The development of pulmonary fibrosis from sarcoidosis often causes major morbidity and mortality and should be a major focus of concern.